The Effect of Liquid Organic Fertilizer “Bio Ferti” Application on the Growth Rate of Spirulina platensis by Using Haldane Model - M Iqbal Maulana Ginting; Eko Agus Suyono; Mochammad Donny Koerniawan; Lucia Tri Suwanti; Ulfah Juniarti Siregar; Arief Budiman (Journal of Tropical Biodiversity and Biotechnology, 2022)
This experimental research was performed to observe the influence of an agricultural liquid organic fertilizer called Bio Ferti on the growth and biomass of Spirulina platensis, aiming at replacing inorganic fertilizer with the liquid organic one. The cultivation of the microalgae was conducted over seven days at Nogotirto Algae Park. The liquid organic fertilizer, namely Bio Ferti, was obtained from the Faculty of Biology, Universitas Gadjah Mada, and prepared to have doses of 2, 4, 6, 8, and 10 mL. For comparison, an inorganic fertilizer with the same doses was also prepared. The variables to be observed were cell density, dry cell weight, and growth kinetics. The culture medium conditions observed were temperature, pH, and salinity (the optimum salinity was 20 ppt). The growth kinetic analysis was performed mathematically using numerical simulations using the Contois and the Haldane models. This research’s results showed that Bio Ferti affected the growth rate of Spirulina platensis. With a dose of 2 mL, it became the optimum medium which produced the highest density and dry weight of 1.78x106 cells/mL and 160 mg/mL, respectively. Meanwhile, the inorganic fertilizer with a dose of 10 mL produced the highest density and dry weight of 2,13x105 and 80 mg/mL, respectively. The temperature ranged from 28 to 31°C, while the pH ranged from 8.01 to 9.02 for each medium. The suitable model to describe the growth kinetics of Spirulina platensis was the Haldane model.